2015
DOI: 10.4238/2015.september.22.23
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation of human osteoblasts from a type 2 diabetic patient in vitro

Abstract: ABSTRACT. We investigated the proliferation and differentiation potential of human osteoblasts from a type 2 diabetic patient in vitro. Human osteoblasts were obtained from a healthy subject and a type 2 diabetic patient and were cultured in vitro using the tissue explant adherent method. Differences in cell morphology were observed under a phase contrast microscope. The osteogenic differentiation capacity was evaluated by alizarin red staining, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…However, our previous study revealed that the migration, proliferation, and osteogenic differentiation ability of BMSCs derived from the jawbone marrow of T2DM patients (DM-BMSCs) was significantly diminished compared to the BMSCs from normal controls (N-BMSCs). 9 , 10 Therefore, enhancing the function of DM-BMSCs and improving the implant success rate are critical for implant surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous study revealed that the migration, proliferation, and osteogenic differentiation ability of BMSCs derived from the jawbone marrow of T2DM patients (DM-BMSCs) was significantly diminished compared to the BMSCs from normal controls (N-BMSCs). 9 , 10 Therefore, enhancing the function of DM-BMSCs and improving the implant success rate are critical for implant surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) play an important role in the process of osseointegration of oral implants by modulating cell proliferation, adhesion and osteogenic differentiation to regulate the remodelling of bone tissue around newly introduced implants (Biguetti et al, 2018; Huo & Yue, 2020; Martínez‐Ibáñez et al, 2018). Jawbone marrow mesenchymal stem cells (JBMSCs) from patients with T2DM exhibit significantly lower proliferation, migration, differentiation and mineralisation activities than cells derived from patients without T2DM (Li et al, 2015). Therefore, the reduced osteogenic differentiation potential of JBMSCs in T2DM patients could be responsible for the failure of osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…After the BMSCs adhere to the implant surface, the osteogenic differentiation process is initiated, and new bone gradually forms with the assistance of cells, blood, and related cytokines [7]. Previous studies have shown that BMSC proliferation, migration, differentiation, and mineralization in T2DM patients are significantly inferior to those in nondiabetic patients [8]. The weakened osteogenic differentiation potential of BMSCs in T2DM patients might be an important reason for the failure of implant osseointegration at the healing stage.…”
Section: Introductionmentioning
confidence: 99%